Impact of Educational Interventions on Nurses’ Knowledge and Practice of the Glasgow Coma Scale: A Systematic Review - Dawran, Shahi; Letchmi Panduragan, Santhna (Journal of Neonatal Surgery, 2025)
Background: The Glasgow Coma Scale (GCS) is a critical neurological assessment tool used by nurses to evaluate patient consciousness levels. However, inconsistencies in nurses' knowledge and practical application of the GCS have been reported in various studies. This meta-analysis aims to assess the level of GCS knowledge among nurses, identify gaps in practical application, and evaluate the effectiveness of educational interventions. Methods: A systematic review of studies on nurses’ GCS knowledge and competency was conducted. A total of 16 studies were included, covering various study designs, including descriptive cross-sectional (50%), quasi-experimental (25%), and cross-sectional (25%) methodologies. Key findings related to GCS knowledge levels, application accuracy, and the impact of training interventions were synthesized. Results: The analysis revealed that while 65% to 71% of nurses demonstrated good theoretical knowledge of GCS, practical application remained inconsistent. A significant proportion (43.75%) of studies reported inadequate GCS knowledge among nurses, while 37.5% found that nurses had moderate to good knowledge but poor assessment accuracy. Studies showed a positive correlation (r = 0.33 to r = 0.52, p < 0.05) between GCS knowledge and assessment accuracy, reinforcing the need for continuous training. Educational interventions significantly improved GCS competency, with post-training improvements reported in 80.6% of nurses in some studies. Persistent challenges were identified in motor response assessment, documentation, and practical application. Conclusion: The findings underscore the urgent need for structured GCS training, competency-based assessments, and curriculum integration. While nurses often possess foundational knowledge, hands-on training, reflective practice, and simulation-based learning are essential for bridging the knowledge-practice gap. Future research should focus on innovative educational strategies and long-term retention of GCS skills to enhance patient safety and neurological assessment accuracy.